Penerapan Prinsip - Prinsip Good Governance Dalam Meningkatkan Kinerja Aparatur Pelayanan Publik di DPMPT SP Kab Klaten - Rio Muhamad; Warsito .; Wachid Abdulrahman (Journal of Politic and Government Studies, 2017)
AbstrackThe applicaion of the principle – principle of good governance to improve theperformance of the public service to become one of the main things to establish goodgovernance in serving the community. The role of employee performance becomevery important because in serving the public employees government be in theforefront in the creation of good governance. Performance employee in the service ofcapital investment and integrated service of Klaten as public servants in the licenceare expected to serve the community in accordance with the rules of the order.Research methods used in this study is the method mix approach technique ofdata collection through the Questionnaire and interviews, the study document. Therespondent in this study was the head of licensing, complaints and capital investment.The research results showed that the application of the pronciple – principleof good governance is in compliance and performance measurement officer in theservice of capital investment and integrated sevice of klaten regency entered in thecriteria of good, the highest indicator is on the level of service and procedures claritylowest indicator exist at the level of the reasonableness of the cost. Overallcommunity satisfaction index against the performance of employees in the service ofcapital investment and licensing integrarted klaten regency that is GOOD.Recommendations which could be awarded against the application of theprinciple – prinple of good governance in inproving the performance of publicservice aparatur in klaten regency is DPMPT SP the service of carrying out the workand response ablity training work periodically for employees with the perpose of theemission and vision of the department could be reached and serve the community inaccordance with the existing.Key Words: Good Governance, Performance Measurement, DPMPTSP, Klaten